Relationship between the Cleanliness of Nails and the Usage of Footwear with the Incidence of Helminths Infections on Elementary Student in Sibolga of 2019 - Roslina Pane; Nurmaini; Lita Sri Andayani (Britain International of Exact Sciences (BIoEx) Journal, 2020)
Soil – Transmitted Helminths (STH) infection is one of the most common infections in the world, especially for the poor society. Worm infections spread through eggs in human feces that contaminate soils where the level of sanitation is bad. Worm infections are widespread in tropical and subtropical regions, one of which is Indonesia. Around 568 million school-age children have high potential for STH because they live in an areas prone to STH infections (WHO, 2017a). Soil Transmitted Helminths Infection is a health problem with a high prevalence in the tropics and subtropics, especially Indonesia. Children with the primary school age are the group that most often suffer from infection because more daily activities are in contact with the soil and in clean living behavior is still low. The purpose of this study is to find out the relationship between sex and Helminths Infection, nail hygiene and using footwear with the incidence of helminthiasis in students in the city of Sibolga. The results obtained from this study are the number of students infected by helminthiasis by 33.82%, based on male gender as many as 20 students (60.6%) of the 44 students examined and the number of infected women as many as 18 students (39.4 %) of 41 female students examined. The results of the category assessment, for the category of nail hygiene with a good 32.94 percent (28 students) and the category is less good at 67.06 percent (57 people). From the bivariate analysis there was no relationship between sex and helminthiasis. The results of nail hygiene analysis, there is a significant relationship between nail hygiene with helminthiasis infection with a value of p = 0.009 and the value of the prevalence ratio of 2.751. Analysis using footwear, there is a significant relationship between the habit of using footwear with helminthiasis infection with a value of p = 0.004 with a prevalence ratio value of 3.195. From the results of the multiple logistic regression test, the most influential value between nail hygiene and using footwear is using footwear with a p value = 0.009 with a constant value of 3.410.